Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.2147/ott.s101456
|View full text |Cite
|
Sign up to set email alerts
|

Association between APE1 Asp148Glu polymorphism and the risk of urinary cancers: a meta-analysis of 18 case–control studies

Abstract: BackgroundSeveral observational studies suggested that APE1 Asp148Glu was significantly associated with urinary cancers; however, the results of published studies are inconsistent.Materials and methodsThe PubMed and EMBASE were searched for case–control studies regarding the association between Asp148Glu and the risk of urinary cancers with a time limit of September 12, 2015. Pooled odds ratios (ORs) and 95% confidence intervals (CIs) were used to assess the strength of the association between Asp148Glu and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…The results of investigations into the association between APE1 gene variations and kidney cancer susceptibility have produced con icting outcomes. In a meta-analysis conducted by Zhong et al, no signi cant in uence of APE1 polymorphism on urinary cancers susceptibility was observed [29]. Similarly, in a study led by Cao and colleagues, a polymorphism located within the promoter region, capable of in uencing gene expression, was not identi ed as a factor linked to kidney cancer [30].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The results of investigations into the association between APE1 gene variations and kidney cancer susceptibility have produced con icting outcomes. In a meta-analysis conducted by Zhong et al, no signi cant in uence of APE1 polymorphism on urinary cancers susceptibility was observed [29]. Similarly, in a study led by Cao and colleagues, a polymorphism located within the promoter region, capable of in uencing gene expression, was not identi ed as a factor linked to kidney cancer [30].…”
Section: Discussionmentioning
confidence: 96%
“…Studies have demonstrated that in cases of acute renal injuries induced by oxidative stress, APE1 expression decreases, leading to the development of renal apoptosis [27]. APE1 is markedly upregulated in various cancer types, and its subcellular localization can vary signi cantly depending on the speci c tissue and stage of tumor development [13,29]. However, the causal relationship between APE1's overexpression and localization in tumors and their role in initiating and advancing cancer, increasing its aggressiveness, and promoting invasion remains a subject of ongoing debate.…”
Section: Discussionmentioning
confidence: 99%
“…It is not yet clear if family history plays a role in bladder cancer development. Research shows that the risk increases for first- and second-degree relatives, yet genetic predisposition is still under investigation [ 4 , 5 , 6 ]. Bladder cancer is usually presented with painless macrohematuria [ 7 ].…”
Section: Introductionmentioning
confidence: 99%